2006
DOI: 10.1001/jama.295.13.1566
|View full text |Cite
|
Sign up to set email alerts
|

Can the Clinical History Distinguish Between Organic and Functional Dyspepsia?

Abstract: Neither clinical impression nor computer models that incorporated patient demographics, risk factors, history items, and symptoms adequately distinguished between organic and functional disease in patients referred for endoscopic evaluation of dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(101 citation statements)
references
References 40 publications
4
90
1
6
Order By: Relevance
“…However, a systematic review of seven studies evaluating over 46,000 dyspepsia patients undergoing upper GI endoscopy found that alarm features had limited value ( 32 ). Alarm features also had limited utility in detecting any organic pathology (malignancy, peptic ulcer disease, or esophagitis) ( 33 ). Individual alarm features such as weight loss, anemia, or dysphagia had sensitivities and specifi cities of ~66% with a positive likelihood ratio of 2.74 (95% CI=1.47-5.24) ( 31 ).…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…However, a systematic review of seven studies evaluating over 46,000 dyspepsia patients undergoing upper GI endoscopy found that alarm features had limited value ( 32 ). Alarm features also had limited utility in detecting any organic pathology (malignancy, peptic ulcer disease, or esophagitis) ( 33 ). Individual alarm features such as weight loss, anemia, or dysphagia had sensitivities and specifi cities of ~66% with a positive likelihood ratio of 2.74 (95% CI=1.47-5.24) ( 31 ).…”
Section: Conditional Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…Patients' history and physical examination are neither sensitive nor specific enough to predict which patients' dyspeptic organic nosology will be detected y endoscopy (144,200) . The low prevalence of cancer in this population and the high rate of irrelevant findings on endoscopy have encouraged the use of empirical treatment (H pylori eradication or a cycle with proton pump inhibitors) before performing an invasive and relatively costly procedure (upper endoscopy with biopsies).…”
Section: Statementmentioning
confidence: 99%
“…13,14 The cost of managing dyspepsia may be reduced if upper GI symptoms could accurately distinguish between organic and functional dyspepsia (FD), but a systematic review has suggested that symptoms perform poorly in this regard. 15 The commonest organic finding at upper GI endoscopy in Western populations with dyspepsia is erosive esophagitis, 16 and over the last 20 years definitions of the condition have been refined substantially, [17][18][19][20] with the main aim of excluding patients with gastro-esophageal reflux disease (GERD), in an attempt to enrich the number of patients with FD.…”
Section: Introductionmentioning
confidence: 99%